RP-HPLC METHOD DEVELOPMENT AND VALIDATION FOR SIMULTANEOUS ESTIMATION OF CURCUMIN AND RESVERATROL IN NANO-MICELLE: DUAL DRUG DUAL FORM SIMULTANEOUS ESTIMATION - RAHAMAN, SK MOSIUR; CHANDRA, ATANU; BISWAS, RANU (International Journal of Applied Pharmaceutics, 2024)
Objective: To develop a reverse-phase high-performance liquid chromatography (RP-HPLC) method for simultaneous estimation of conjugated form of Curcumin (CCMN) and free form of Resveratrol (RSV) in nano-micelle. Methods: The conjugation of lipophilic CCMN and hydrophilic Chitosan (CHT) through succinyl linker produce amphipathic molecule that can self-assemble into RSV solution to form micelle. Here RSV exists in micelle core as free form and CCMN with micelle backbone as conjugated form. So it required to estimate conjugated drug and free drug simultaneously from nano-micelle. We developed a RP-HPLC method, utilized C18 column, follow flow rate of mobile phase 1.0 ml/min, which consist of acetonitrile with water (0.5% Ortho Phosphoric acid, pH 4.6) in the ratio of 1:1 for 20 min. Injection volume was 10μl and column temperature 25 ℃. Isosbestic detection of both drugs was at 254 nm. Results: The retention time of RSV and CCMN were at 8.15 min and 11.41 min respectively, completely distinguished sharp peak of CCMN and RSV developed with resolution 7.360±0.117, wide range of linearity with correlation coefficient value (R2) of CCMN and RSV were 0.99987 and 0.99992 respectively and recovery value of CCMN and RSV were 100.041±0.22 % and 100.041±0.21 % respectively. The RSD (relative standard deviation) for accuracy, precision and robustness of the method was found to be less than 2%. Conclusion: The develop method for simultaneous estimation of conjugated CCMN and free form of RSV in the nano-micelle formulation was consider to be accurate, precise, robust and sensitive.